Effect of six weeks of dura disc and mini-trampoline balance training on postural sway in athletes with functional ankle instability - Kidgell, D. J.; Horvath, D. M.; Jackson, B. M.; Seymour, P. J. (The Journal of Strength and Conditioning Research, 2007)
Lateral ankle sprain (LAS) is one of the most common injuries incurred during sporting activities, and effective rehabilitation programs for this condition are challenging to develop. The purpose of this research was to compare the effect of 6 weeks of balance training on either a mini-trampoline or a dura disc on postural sway and to determine if the mini-trampoline or the dura disc is more effective in improving postural sway. Twenty subjects (11 men, 9 women) with a mean age of 25.4 +/- 4.2 years were randomly allocated into a control group, a dura disc training (DT) group, or a mini-trampoline (MT) group. Subjects completed 6 weeks of balance training. Postural sway was measured by subjects performing a single limb stance on a force plate. The disbursement of the center of pressure was obtained from the force plate in the medial-lateral and the anterior-posterior sway path and was subsequently used for pretest and posttest analysis. After the 6-week training intervention, there was a significant (p < 0.05) difference in postural sway between pre-and posttesting for both the MT (pretest = 56.8 +/- 20.5 mm, posttest = 33.3 +/- 8.5 mm) and DT (pretest = 41.3 +/- 2.6 mm, posttest = 27.2 +/- 4.8 mm) groups. There was no significant (p > 0.05) difference detected for improvements between the MT and DT groups. These results indicate that not only is the mini-trampoline an effective tool for improving balance after LAS, but it is equally as effective as the dura disc.